Development of ELKPD Based on a Learning Model Sole Using Liveworksheet for Reaction Rate Material in Second Grade Senior High School - Shyiba Yunia Aliffah; Herdini Herdini; Sri Haryati (International Journal of Educational Evaluation and Policy Analysis, 2025)
This study aims to produce a valid SOLE-based reaction rate electronic student activity sheet (E-LKPD) and to determine user responses to the resulting product. The research method used is research and development (R&D) using the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model. The research instrument is a validation sheet given to three validators and a user response sheet to one chemistry teacher of Senior High School 7 Pekanbaru and one chemistry teacher of Senior High School 11 Pekanbaru as well as 13 class XI students of Senior High School 7 Pekanbaru and 13 class XI students of Senior High School 11 Pekanbaru. The data analysis technique is carried out by calculating the percentage of validation assessment scores and user responses, the results of which are measured by an attitude assessment table. The results of the study indicate that the electronic student activity sheet (E-LKPD) based on SOLE that was developed has met the valid criteria by the material validator based on the aspect of content feasibility of 92.19%, SOLE model characteristics of 95.83%, pedagogic of 93.75%, linguistic of 95.83% and graphic of 95.83%. For the media validator based on the aspect of size of 100%, cover design of 92.50% and content design of 97.50%. While the user response based on teacher and student responses is in the very good criteria with scores of 94.79% and 88.05% respectively.